Spoon - Terragni, Emilia, ....- (London ; New York : Phaidon, 2002)
Spoon is a definitive view of new product design, presenting the work of 100 exceptional designers who have emerged on an international platform as recently as the last five years: these are selected by 10 critics, designers and entrepreneurs who are universally respected for their informed opinion on the international contemporary design scene.
Covers are composed of steel.
Includes index.
Keywords: Industrial design; Industrial designers